The Effect of Audio-Visual Media on Learning Outcomes in Arts, Culture, and Crafts Education: A Quasi-Experimental Study in Indonesian Elementary Schools - Sela Selfia; Yun Ratna Lagandesa; Muhammad Aqil; Zulnuraini Zulnuraini; Dyah Rahmawati; Surahman Wilade (Journal of Innovation and Research in Primary Education, 2026)
Arts, Culture, and Crafts (SBdP) education in rural Indonesian elementary schools faces persistent challenges due to reliance on conventional lecture-based instruction, resulting in suboptimal student engagement and learning outcomes. Audio-visual media offers potential pedagogical advantages through dual-channel information processing, yet empirical evidence regarding its effectiveness in elementary arts education remains limited. This study investigated the effect of audio-visual media on second-grade students' learning outcomes in SBdP at Parigimpu'u Public Elementary School. A quasi-experimental design with nonequivalent control groups was employed, involving nine students divided into experimental (n=5) and control (n=4) groups. The experimental group received instruction incorporating audio-visual media demonstrating piggy bank construction techniques, while the control group received conventional instruction. Performance-based assessments measuring accuracy, neatness, creativity, and timeliness were administered as pretest and posttest. Data were analyzed using descriptive statistics and independent samples t-test. The experimental group achieved significantly higher posttest scores (M=95.83, SD=2.95) compared to the control group (M=85.94, SD=6.99), with statistical analysis confirming significance (t=2.975, p<0.05). All experimental group students surpassed the minimum passing threshold, demonstrating substantial improvement from baseline. Audio-visual media significantly enhances learning outcomes in elementary SBdP education by facilitating concrete visualization, reducing cognitive load, and promoting active engagement, supporting its integration into arts curricula particularly in resource-constrained rural schools.